Enhancement Supply Chain Control Tower to Reduce Inventory Parts of Heavy Equipment at PT The Biggest Heavy Equipment Company in Indonesia - Dwiyana, Meidi; Kusumastuti, Ratih Dyah; Bustaman, Yosman (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
As a leading heavy equipment distributor in Indonesia, PT. The Biggest Heavy Equipment Company in Indonesia is very concerned about after-sales service as an advantage compared to competitors. Keeping the service level based on target but, it was accompanied by a decrease in working capital as one of the goals of PT. The Biggest Heavy Equipment Company in Indonesia that was establishing a tower in its supply chain concept. This research was conducted at PT. The Biggest Heavy Equipment Company in Indonesia as the owner of the largest market share of heavy equipment in Indonesia. This thesis analyzed the performance of the Supply Chain Control Tower process in the company by using the Supply Chain Operations Reference (SCOR) 12.0 framework. PT. The Biggest Heavy Equipment Company in Indonesia manages supply chain business as a stocked product business, where the company prepares a number of inventories to ensure customer purchasing needs. The results of the analysis at SCOR level 1 show that all strategic metrics are below the set targets. So that at SCOR level 2, an in-depth analysis is carried out with Geographic maps and Thread diagrams that show potential problems in Enable Process (sE2), Plan Source (sP2) and Delivery (sD1) activities. Finally, results of SCOR level 3 analysis using a fishbone diagram reveal that the root cause of the problem is leak of internal company supply chain management, and we recommend to suggest the strategy for enhancement supply chain control tower at PT the Biggest Heavy Equipment Company in Indonesia.